FENOMENA FEAR OUT MISSING OUT (FOMO) TERHADAP KEPUTUSAN PEMBELIAN RESTORAN VIRAL KAREN’S DINER JAKARTA - Wachyuni, Suci Sandi; Namira, Siti; Respati, Rella Dwi; Teviningrum, Shinta (Pusat Penelitian & Pengabdian kepada Masyarakat, Politeknik Pariwisata Bali, 2024)
In the current era of disruption 5.0, uploading digital information about a place to eat to social media users has become a cultural symbol that can depict a lifestyle. This phenomenon makes users afraid of missing out on the latest information and experiences, such as the emergence of Karen's Diner Jakarta restaurant, which went viral on social media. This study analyzes the phenomenon of FOMO (fear of missing out) in consumer purchasing decisions. With a quantitative approach through an online survey, this study captured 100 respondents selected based on purposive sampling. The population of this research is the people of Jakarta, who are potential consumers. Meanwhile, the sample of this research is consumers who have made purchases at Karen's Diner Restaurant. The survey instrument includes questions about FOMO variables and purchasing decisions and is measured on a Likert scale. The data were analyzed using descriptive analysis, regression test, and hypothesis t-test. The study results show that FOMO positively affects purchasing decisions by 60%. This research shows the theoretical implication that the FOMO phenomenon, which includes a person's fear and worry of missing out on something new, affects purchasing decisions. Therefore, viral marketing has a significant impact on restaurant sales. The practical implication of this research is a recommendation for food and beverage businesses maximize digital and viral marketing.